Clinico-Epidemiological Fetaures of Pityriasis Alba in Six- to Sixteen- Year Old Children in Public Schools in Manuel A. Mesones-Muro District. Lambayeque, Perú - Castillo-Mori, Ysabel (2011)
Objective: To describe clinical and epidemiological features of pityriasis alba in a 6- to 16- year old population of students from public schools in Mesones-Muro district, from March to June 2010. Materials and methods: This is a descriptive, prospective and cross-sectional study. We collected clinical and epidemiological data, including associated diseases and clinical history in a specially designed form, which was administered to parents and/or guardians. We used the Epidat v. 3.1 software, in order to find the kappa index which indicated the reliability of agreement between raters. We surveyed the whole 6- to 16- year old schoolchildren population from public schools belonging to this district educational jurisdiction. We used descriptive and analytical statistics, and significance was fixed with using a p <0.05 value. SPSSv.17.0. software was used for data analysis. Results: Out of 548 students assessed, 390 (71.2%) had pityriasis alba. Their average age was 10.16 ± 2.99 years, 52.6% were male, and 55.1% were adolescents. Facial lesions were found in 93.6%, multiple lesions in 92.3%, the skin phototype IV was most frequently affected (61.8%), and the time with the condition was 5.34 ± 6.85 years. We found an association between pityriasis alba and the following conditions: acne, a history of atopy, and a family history of pityriasis alba and allergic rhinitis, according to chi2 testing and Fishers exact test all with p <0.05. Conclusions: Pityriasis alba is a common problem in Mesones-Muro district. Its epidemiological characteristics differ from those found in other populations, but its clinical features are similar to those reported in other populations. There was an association between pityriasis alba with associated conditions, such as acne and a history of atopy, but there was no association between pityriasis alba and sex and life development stages.